Factores de la gestión del talento humano con mayor incidencia en la rentabilidad de las organizaciones (2018)
In the current environment, organizations are immersed in aggressive environments, in which conditions fluctuate from one moment to another. It is for this reason that organizations must establish strategies that are as flexible as the market, if they want to be leaders in the environment in which they participate. At present, companies must enhance their human capital if they want to be competitive and achieve a distinction, because due to the advancement in technology and the globalization process in which we find ourselves, human resources are the most important asset.